Evaluating the Implementation of Balanced Scorecard in Employee Performance Appraisal - Ganang, Trystania; Simbolon, Netty Laura; Mangani, Ktut Silvanita (Journal The Winners, 2024)
One well-known performance assessment approach is the balanced scorecard (BSC), which evaluates financial and non-financial performance aspects. Although BSC has been widely used in the private sector, its implementation in the public sector presents unique challenges. The research examined the implementation of BSC at Perum Perhutani, an Indonesian state-owned company that manages forest resources. The research focused on the implementation of BSC in the Human Resources (HR) division. Even though BSC has succeeded in improving overall performance assessment, there are still obstacles to employees' understanding of the BSC concept, which causes employees to be confused when interpreting performance indicators. Apart from that, performance assessments are still affected by subjective assessments and a lack of specific and clear indicators. The research proposes the integration of Objectives and Key Results (OKR) to increase the clarity and alignment of performance indicators. By employing NVivo 12 for analysis, the research contributes to the literature regarding BSC implementation in developing countries, especially in the public sector, offering new insights to improve performance management practices in Indonesia.